Предмет: Алгебра,
автор: АрсЛев
Упростите выражение
(ab-1-a-1b)(a-b)-1
Ответы
Автор ответа:
0
( ab - 1 - a - b)(a - b) - 1 = a^2b - ab^2 - a + b - a^2 + ab - ab + b^2 - 1 =
= a^2b - ab^2 - a + b - a^2 + b^2 - 1.
= a^2b - ab^2 - a + b - a^2 + b^2 - 1.
Автор ответа:
0
варианты ответов
Автор ответа:
0
1)ab/a-b 2)a+b 3)ab/a+b 4)ab 5)a+b/ab
Автор ответа:
0
вы не правильно решили
Похожие вопросы
Предмет: Русский язык,
автор: Avalebedeva
Предмет: Русский язык,
автор: hfhghfghgjhghfjgfhfg
Предмет: Математика,
автор: dimaevamerem
Предмет: Алгебра,
автор: yana777888